Time, transition, and planetary decolonial justice as invention - Agathangelou, Anna M. (Environmental politics, 2024)
Contestations over temporal categories are marginalized in transition debates. This article reorients such debates by exploring the structural relationship between time and just transition or planetary justice. I demonstrate how transition, defined as governments and inter-state institutions' efforts to shift to a lower carbon future, is inscribed with categories of time and certain notions of justice. I argue the recent acknowledgement of the link of colonization with climate change by the Intergovernmental Panel on Climate Change does not necessarily disrupt the deployment of a linear and recursive (universal) notion of capital time nor does it challenge the co-constitution of racialized accumulation institutions and governance power technologies, with dire effects on a 'just transition.' I then draw on Frantz Fanon's idea of invention as an event without sense or content, a decolonial violence whose subject plunges into an abyss and whose 'measure' or possibility is always unprecedented.